On the Quality of Foreign Language Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes ways to improve the quality of teaching a foreign language, in particular English, and the need to adapt the content of the lesson for medical university students to their professional needs. It is shown that during the lesson, students should master medical terminology, be actively involved in communication, and develop their speech skills. The author substantiates that the personal and professional qualities of the teacher, thorough preparation for the lesson, the development of dialogues, work on lexical material, and a creative approach play an important role in increasing the effectiveness of the lesson.